Entrepreneurial Motivation in the Fourth Industrial Revolution - Wardani , Shanti Ike; Latifah, Nunuk (KnE Social Sciences, 2021)
This study aimed to analyze the entrepreneurial motivation of members of Pemberdayaan Kesejahteraan Keluarga (PKK) in the Trenggalek Regency during the fourth industrial revolution. A descriptive qualitative approach was used. Data collection involved interviews and triangulation techniques. The results indicated that people are motivated to start a business because there is the hope of making a profit to meet their needs. By being an entrepreneur, a person is free to carry out their affairs in their way, enjoy their profits, gain additional income, and be free of the rules of the organization/company, intervention or influence of others. Also, people want to be an entrepreneur because they have a sense of pride in being able to be independent in making capital, managing supervision and being a leader for themself, and trying to get out of the challenges of their life without expecting help from others. However, people who try to become entrepreneurs in the fourth industrial revolution face challenges. It is necessary to increase the government’s participation in creating new entrepreneurs to face these challenges. One approach is providing training to equip the community with skills and abilities in utilizing the resources they have. It is important to change the mindset of the community to become entrepreneurs. Keywords: entrepreneurship, industrial revolution, motivation